1972
DOI: 10.1159/000230872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Viable and Non-viable Measles Virus on Proliferating Human Lymphocytes

Abstract: In vitro addition of an autoclaved noninfective measles virus preparation to cultured lymphocytes markedly inhibited the cellular proliferation induced by phytohemagglutinin or tuberculin, as measured by lymphoblastic transformation, and incorporation of tritiated thymidine and uridine. This suppression was greater than that exerted by live virus and was dose-dependent. No gross evidence of cytotoxicity was observed, as measured by changes in cell number or trypan blue exclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1
1

Year Published

1974
1974
1981
1981

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
2
8
1
1
Order By: Relevance
“…This was shown to be the result of an inhibitory factor in acute phase serum, for the lymphocytes responded normally to an optimum dose of PHA in convalescent serum or FCS. This conclusion contradicts experimental evidence (10,12) which suggests that the decreased [3H]thymidine uptake is the result of direct viral inhibition of host-cell DNA synthesis, an effect which is only achieved with an unnaturally large dose of virus. Viability counts showed this inhibition was not a result of killing of lymphocytes.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This was shown to be the result of an inhibitory factor in acute phase serum, for the lymphocytes responded normally to an optimum dose of PHA in convalescent serum or FCS. This conclusion contradicts experimental evidence (10,12) which suggests that the decreased [3H]thymidine uptake is the result of direct viral inhibition of host-cell DNA synthesis, an effect which is only achieved with an unnaturally large dose of virus. Viability counts showed this inhibition was not a result of killing of lymphocytes.…”
Section: Discussioncontrasting
confidence: 57%
“…However, Finkel and Dent (7) noted impairment of lymphocyte response to suboptimal doses of PHA but were unable to show that this was because of serum inhibitory factors that are known to occur in some viral infections (8). Experiments by Zweiman and Miller (9)(10)(11) demonstrated that both live and killed measles virus could suppress the response of human lymphocytes to PHA and purified protein derivative (PPD). Sullivan et al (12) extended this work and postulated that depression by live virus of lymphocyte stimulation by PHA resulted from direct viral inhibition of host cell DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of suppression of host DNA synthesis by measles virus has also been reported by some investigators. Zweiman and Miller [15] reported that autoclaved measles virus could inhibit the cellular DNA synthesis of phytohemagglutinin (PHA)-stimulated lymphocytes and that the suppressive activity was found in both dialyzable and nondialyzable fractions of autoclaved measles virus. DSF also inhibited the cellular DNA synthesis of PHA-stimulated lymphocytes of mice (unpublished data) and continuous human lymphoid cells (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…As to the mechanisms of measles virus-induced immunosuppression in humans, the following possibilities have been speculated: (1) direct suppression of the lymphocyte function by infectious virus (Sullivan et al, 1975), (2) a suppressive factor of low molecular weight in the measles virion (Zweiman, 1972), (3) suppression of the macrophage function (Finkel and Dent, 1973), and (4) shortage of T-cell pool caused by a recruitment of T cells to the site of virus growth (Burnet, 1968).…”
Section: Discussionmentioning
confidence: 99%